Air up there. I.H.T. the new force in altitude training - Cedaro, R. (1999)
Intermittent Hypoxic Training or IHT which has its origins in the Russian military and aero-space programs may well herald the new frontier in altitude training. Approximately 18 months ago this form of altitude simulation was introduced to New Zealand sports by Dr. Alexei Korolev of the former Soviet Union. This method of altitude training which is claimed to be equivalent and even superior to conventional altitude training by being able to control the altitude dose isn achieved by exposing athletes to hypoxic air containing 9-16% oxygen (equating to altitude exposures of 2,000 to 6,500 metres above sea level) intermittently at 4-6 minute intervals interspersed with breathing normoxic air for the same periods, for 60-90 minutes per session, once or twice a day. Exposing the athlete to such hypoxic gases in the aforementioned manner, via a machine called an hypoxicator, is thought, among other physiological and biochemical reactions, to stimulate EPO release and hence red blood cell production resulting in increased oxygen carrying capacity within the blood.